2009
DOI: 10.1007/s00442-009-1436-4
|View full text |Cite
|
Sign up to set email alerts
|

How leaf-cutting ants impact forests: drastic nest effects on light environment and plant assemblages

Abstract: Leaf-cutting ants (Atta spp.) have become a topical issue in Neotropical ecology, particularly because they are reaching hyper-abundance due to escalating levels of fragmentation in recent years. Yet, despite intensive research on their role as dominant herbivores, there is still insufficient documentation on the impacts of their large, long-lived nests on plant assemblage structure and ecosystem functioning. Our study aimed at investigating the magnitude, nature, and spatial extent of nest influence by assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
120
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(132 citation statements)
references
References 42 publications
7
120
1
1
Order By: Relevance
“…While other studies have suggested that leaf-cutting ants may act as ecological engineers affecting vegetation patterns (Farji-Brener and Illes 2000;Wirth et al 2003;Correa et al 2010), few works have experimentally tested this hypothesis, and none have specifically linked that idea with the likelihood of biological invasions. Using a representative number of plant species of the study area, we experimentally demonstrated that exotics gain *100% more leaf and root biomass than natives when both kinds of species grow in RDs, suggesting that leaf-cutting ant nests may promote the invasion of exotic plants.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…While other studies have suggested that leaf-cutting ants may act as ecological engineers affecting vegetation patterns (Farji-Brener and Illes 2000;Wirth et al 2003;Correa et al 2010), few works have experimentally tested this hypothesis, and none have specifically linked that idea with the likelihood of biological invasions. Using a representative number of plant species of the study area, we experimentally demonstrated that exotics gain *100% more leaf and root biomass than natives when both kinds of species grow in RDs, suggesting that leaf-cutting ant nests may promote the invasion of exotic plants.…”
Section: Discussionmentioning
confidence: 95%
“…Although leaf-cutting ants have been proposed as ecological engineers (Wirth et al 2003;Correa et al 2010), studies of their effects under this conceptual framework, including their potential impact on exotic plant species, are still lacking (e.g., absent in the review of Hastings et al 2007). Earlier evidence suggests that engineering activities by leaf-cutting ants may promote biological invasions.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Leaf-cutting ants (genera Acromyrmex and Atta) are major defoliators in the Neotropics, removing at least 2% of annual leaf production and impacting the distribution of resources in habitats where they occur (Farji-Brener 2001, Herz et al 2007a, Corrêa et al 2010. The ants collect tissue from a diverse group of plants and therefore interact with a vast number of endophytes.…”
Section: Introductionmentioning
confidence: 99%
“…are considered conspicuous herbivores in the neotropics [1,2]. Their role in the ecosystem, however, goes well beyond their herbivory because their construction and maintenance of nests causes diverse impacts to soil [3,4] with consequences for recruitment dynamics, [5][6][7][8][9] nutrient access [10,11], and growth of nearby vegetation [12].…”
Section: Introductionmentioning
confidence: 99%